Penerapan Pendekatan Multisensori Menggunakan Media Loose Part Dalam Menstimulasi Literasi Anak Usia 5-6 Tahun Di TK Multazam - Misno, Ananda TRisnawati; Ilyas, Siti Nurhidayah; Asri, Sri Wahyuni (Universitas Islam Negeri Jurai Siwo Lampung, 2025)
This study aims to describe the application of multisensory methods using loose parts media to stimulate literacy in children aged 5–6 years at TK Multazam. The research method used is a descriptive qualitative approach with data analysis through 1. Reduction, 2. Presentation of data which is data collection, 3. Verification which is the conclusion. The subjects in this study are the classroom teacher and the school principal. The research results show that: In the implementation of literacy learning at TK Multazam, a multisensory approach combined with the use of loose parts media has proven to be an effective strategy to stimulate the literacy development of early childhood. The results indicate that teachers actively apply this method through activities involving various senses of children such as visual (sight), auditory (hearing), and kinesthetic-tactile (touch movement), and loose parts are an important component of classroom learning. Each class is equipped with various types of loose part materials because loose parts can enhance children's creativity, imagination, and cooperation.